Electromyographic activity of beating and reaching during simulated boardsailing - Buchanan, M.; Cunningham, P.; Dyson, R. J.; Hurrion, P. D. (Journal of Sports Sciences, 1996)
This study examined the responses of six competitive boardsailors (three males, three females) during laboratory-based simulation tasks while the electromyographic activity of up to 13 muscles was recorded. A sailboard, mounted in a steel frame and resting on a waterbed, allowed simulation of roll and pitch movements. Wind force was simulated by attaching the boom to a weight stack with a hydraulically controlled buffered release phase. The progression of the simulation test was controlled by the sailor copying movements on an edited video of each subject boardsailing on the open water. Analysis of individual pumping movements for mean peak percentage of maximal enveloped voluntary contraction (%MEVC) in `beating' and `reaching' showed that muscular activity in the arm (flexor carpi ulnaris, extensor carpi radialis and biceps brachii) was greatest (66-94% MEVC), with considerable activity (58-75% MEVC) in the deltoid and trapezius shoulder muscles, but much less activity in the leg muscles (16-40% MEVC). For the combined upper and lower body muscles there was a significant difference (P < 0.001) between `beating' and more physically demanding `reaching' pumping activity. Electromyographic activity was higher than reported previously during simulation, reflecting the current dynamic nature of the sport.